2019
DOI: 10.3390/app9224769
|View full text |Cite
|
Sign up to set email alerts
|

A Deep-Learning-Based Vehicle Detection Approach for Insufficient and Nighttime Illumination Conditions

Abstract: Most object detection models cannot achieve satisfactory performance under nighttime and other insufficient illumination conditions, which may be due to the collection of data sets and typical labeling conventions. Public data sets collected for object detection are usually photographed with sufficient ambient lighting. However, their labeling conventions typically focus on clear objects and ignore blurry and occluded objects. Consequently, the detection performance levels of traditional vehicle detection tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 13 publications
(85 reference statements)
0
15
0
Order By: Relevance
“…Yazdi and Bouwmans [20] compared various moving object detection methods with a focus on the case of a moving camera. Some studies utilized training techniques to detect objects from video [21][22][23]. Zhang et al used a structural feature to construct a shape model to detect objects [24].…”
Section: Related Workmentioning
confidence: 99%
“…Yazdi and Bouwmans [20] compared various moving object detection methods with a focus on the case of a moving camera. Some studies utilized training techniques to detect objects from video [21][22][23]. Zhang et al used a structural feature to construct a shape model to detect objects [24].…”
Section: Related Workmentioning
confidence: 99%
“…Their methods significantly outperformed the original SSD detection model. Leung et al modified the faster region-based CNN model to detect vehicles in nighttime and insufficient illumination conditions [21]. The experimental results demonstrated that the proposed method could achieve high detection accuracy in various illumination conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Another approach for this issue is to collect specific data to retrain the deep learning model. Leung et al [ 25 ] collected nighttime images by themselves and labeled all of them to develop a nighttime vehicle dataset. With the dataset, they trained the neural network and obtained a model that achieved the purpose of detecting vehicles with multiple classes.…”
Section: Introductionmentioning
confidence: 99%